Pengaruh Persepsi Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Warmindo Kotlam, Kota Lama Semarang - Khoirulloh, Hamid (Institut Agama Islam YPBWI Surabaya, 2025)
. The purpose of this research is to determine the influence of price perceptions and service quality on consumer purchasing decisions at Warmindo Kotlam Semarang. The population in this study was consumers of Warmindo Kotlam Kota Lama Semarang with a sample size of 95 which was determined using a purposive sampling technique. The results of the analysis stated that all questionnaire items as research instruments were valid and reliable. Hypothesis testing found that price perception had a significant influence on purchasing decisions at Warmindo Kotlam Kota Lama Semarang, service quality had a significant influence on purchasing decisions at Warmindo Kotlam Kota Lama Semarang. The F test states that the research model for the influence of the independent variable on the dependent variable is appropriate. The coefficient of determination test shows that perceptions of price and service quality are able to explain purchasing decisions by 39.3%.